New understandings of ethanol oxidation reaction mechanism on Pd/C and Pd2Ru/C catalysts in alkaline direct ethanol fuel cells - Guo, Junsong (2018)
Ethanol oxidation reaction (EOR) on Pd2Ru/C and Pd/C catalysts in alkaline media is studied comprehensively by cyclic voltammetry, chronoamperometry, in situ FTIR, single fuel cell test and electrochemical impedance spectroscopy measurements. The results show that, as compared to Pd/C, Pd2Ru/C favors acetaldehyde formation and hinders its oxidation. Based on X-ray absorption data, which evidence that Ru promotes a larger electronic vacancy of the Pd 4d band, it is expected that the formation of adsorbed ethoxy is favored on Pd2Ru/C and followed by its oxidation to acetaldehyde facilitated by oxygenated species provided by Ru. In contrast, acetaldehyde oxidation is more difficult on Pd2Ru/C than on Pd/C likely because the adsorption energy of the reactive species is increased. We also show that the performance of Pd2Ru/C anode in alkaline direct ethanol fuel cell (ADEFC) is initially better but degrades much more rapidly than that with Pd/C anode under the same test conditions. The degradation is demonstrated to result from the accumulation of large amounts of acetaldehyde, which in alkaline media forms dimers by the aldol condensation reaction. The dimers tend to be responsible for blocking the active sites for further ethanol oxidation. This comprehensive study provides new understandings of the roles of Ru in Pd2Ru/C for EOR in alkaline media, unveils the causes of the performance degradation of fuel cells with Pd2Ru/C and demonstrates that initial good performances are not necessarily a valid criterion for selecting appropriate anode catalysts for ADEFC applications.